Self-assembly material, solar cell and electric equipment
By passivating the perovskite interface using a first self-assembled molecular material containing aryl group coordination atoms, the problem of limited passivation effect in the prior art is solved, and higher photoelectric conversion efficiency and stability are achieved.
Patent Information
- Application Number
- CN202311252001.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
The existing self-assembled materials have limited passivation effect on perovskite interfaces, resulting in insufficient photoelectric conversion efficiency and stability of perovskite solar cells.
A self-assembly material including a first self-assembly molecular material is used, and the structure of the material contains an aryl group (Ar) as a coordination atom, and Ar includes a phosphorus atom, arsenic atom, sulfur atom or selenium atom to form a strong coordination bond and passivate the low-coordinated lead at the perovskite interface.
By improving the passivation effect of the perovskite interface, the photoelectric conversion efficiency and stability of solar cells are significantly improved.
Smart Images

Figure CN119698165A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to self-assembly materials, solar cells and electrical equipment. Background Art
[0002] With the rapid development of new energy technologies, solar cells have been widely used in military, aerospace, industry, commerce, agriculture, communications and other fields. Perovskite solar cells have gradually become a hot topic in the research of the new generation of solar cells due to their advantages such as high photoelectric conversion efficiency, simple manufacturing process, low production cost and material cost.
[0003] Among them, there are a large number of defects on the perovskite interface, which affects the photoelectric conversion efficiency and stability of perovskite solar cells. To improve the photoelectric conversion efficiency and stability of perovskite solar cells, self-assembly materials can be used to passivate the perovskite interface. However, the existing self-assembly materials have limited passivation effects on the perovskite interface. Summary of the invention
[0004] The main technical problem solved by the present application is to provide a self-assembly material, a solar cell and an electrical device to improve the passivation effect on perovskite, thereby improving the photoelectric conversion efficiency and stability of the solar cell.
[0005] In order to solve the above technical problems, a technical solution adopted in the present application is: to provide a self-assembling material, including a first self-assembling molecular material, wherein the structural formula of the first self-assembling molecular material is Wherein, Ar represents an aromatic group, Ar includes at least one coordinating atom, the coordinating atom contains unbonded lone pairs of electrons, and the coordinating atom includes one or more of a phosphorus atom, an arsenic atom, a sulfur atom, and a selenium atom; L includes one or more of a carbon-containing group, a nitrogen-containing group, an oxygen-containing group, a silicon-containing group, a phosphorus-containing group, and a sulfur-containing group, and the value of n is 0-10; A includes a hydrophilic group.
[0006] The Ar group of the first self-assembled molecular material is used to contact the light absorption layer of the solar cell to passivate and improve the surface defects of the light absorption layer. By introducing one of phosphorus atoms, arsenic atoms, sulfur atoms, and selenium atoms as a coordination atom in the Ar group, the atomic radius of the coordination atom is relatively large, and the unbonded lone pair of electrons in the coordination atom can combine with the low-coordinated lead vacancies in the light absorption layer to form a strong coordination bond, thereby achieving passivation of the low-coordinated lead in the light absorption layer and reducing defects on the interface of the light absorption layer, so that the solar cell has a higher photoelectric conversion efficiency and better stability.
[0007] In one embodiment, Ar includes two or more coordination atoms, which can provide more coordination sites to passivate more interface defects and enhance the passivation effect of the first self-assembled molecular material on perovskite.
[0008] In one embodiment, Ar is any one of the following Ar1 to Ar12:
[0009]
[0010]
[0011] Among them, X 1 To X 5 Selected from -CR" 2 -、-NR”-、-O-、-SiR” 2 -, -PR”-, -S-, -As-, -Se-, -C(=O)-, -C(=S)-, -C(=NR”)-, -C(=CR” 2 )-, the value of m is 1-3; R 1 To R 143 and R" are independently selected from hydrogen, halogen, -OR', -OCOR', -NHCOR', -NR' 2 , R', halogen-substituted R', -SR', -PR' 2 , -AsR' 2 , -Se-; R' is any one of substituted or unsubstituted phenyl, thienyl, and C1-C5 alkyl.
[0012] By making Ar any one of Ar1 to Ar12, the selection diversity of the first self-assembly molecular material is increased, the affinity of the first self-assembly molecular material to the light absorption material precursor solution can be enhanced, and at the same time, it is conducive to uniform coating over a large area and improves preparation efficiency.
[0013] In one embodiment, when Ar is Ar1, R 1 To R 8 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0014] When Ar is Ar2, R 9 To R 18 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0015] When Ar is Ar3, R 19 To R30 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0016] When Ar is Ar4, R 31 To R 44 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0017] When Ar is Ar5, R 45 To R 60 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0018] When Ar is Ar6, R 61 To R 78 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0019] When Ar is Ar10, and X 1 When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 127 To R 134 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0020] When Ar is Ar11, and X 2 To X 3 When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 135 To R 138 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0021] When Ar is Ar12, and X 4 To X 5 When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 139 To R 143 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 、-Se-.
[0022] By selecting the groups in Ar1 to Ar12 as above, Ar includes at least one phosphorus atom coordination atom, one sulfur atom coordination atom, one arsenic atom coordination atom or one selenium atom coordination atom, thereby improving the passivation ability of the light absorption layer compared with the prior art.
[0023] In one embodiment, when Ar is Ar1, R 1 To R 8 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0024] When Ar is Ar2, R 9 To R 18 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0025] When Ar is Ar3, R 19 To R 30 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0026] When Ar is Ar4, R 31 To R 44 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0027] When Ar is Ar5, R 45 To R 60 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0028] When Ar is Ar6, R 61 To R 78 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0029] When Ar is Ar7, R 79 To R 92 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0030] When Ar is Ar8, R 93 To R 108 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0031] When Ar is Ar9, R 109 To R 126 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0032] When Ar is Ar10 and X 1 When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 127 To R 134 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; or when Ar is Ar10 and X 1 When it contains one of the elements phosphorus, sulfur, arsenic, and selenium, R 127 To R 134 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0033] When Ar is Ar11 and X 2 To X 3 When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 135 To R 138 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; or when Ar is Ar11 and X 2 To X 3 When it contains one of the elements phosphorus, sulfur, arsenic, and selenium, R 135 To R 138 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or,
[0034] When Ar is Ar12 and X 4 To X 5 When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 139 To R 143 At least two of them are selected from -PR' 2、-SR'、-AsR' 2 , -Se-; or when Ar is Ar12 and X 4 To X 5 When it contains one of the elements phosphorus, sulfur, arsenic, and selenium, R 139 To R 143 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , one of -Se-.
[0035] By making the above selection for the groups in Ar1 to Ar12, Ar includes at least two coordinating atoms among phosphorus atoms, sulfur atoms, selenium atoms and arsenic atoms, which can provide more coordination sites to passivate more interface defects of the light absorption layer and enhance the passivation effect of the first self-assembled molecular material on perovskite.
[0036] In one embodiment, the hydrophilic group includes one or more oxygen acid groups, and the oxygen acid groups are anchored to the film layer on the side of the light absorbing layer away from the second electrode to achieve self-assembly; the selection of oxygen acid groups as anchoring groups can reduce the difficulty of the synthesis process. The oxygen acid groups can be orderly arranged on the conductive glass substrate to form a self-assembled molecular film; or can be in contact with the metal oxide hole transport layer, orderly arranged on the metal oxide hole transport layer to form a self-assembled molecular film, and at the same time passivate the surface defects of the metal oxide hole transport layer.
[0037] In one embodiment, the oxygen acid group includes -COOH, a salt corresponding to -COOH, -PO(OH) 2 、-PO(OH) 2 The corresponding salt, -PHO(OH), the corresponding salt of -PHO(OH), -SO 2 (OH), -SO 2 (OH) corresponding salt, -B(OH) 2 、-B(OH) 2 By making the oxygen acid group any of the above, the selection diversity of the first self-assembly molecular material is increased, the affinity of the anchoring group and the film layer on the side of the light absorbing layer away from the second electrode can be improved, and the anchoring strength can be enhanced.
[0038] In one embodiment, L is -CR" 2 -、-NR”-、-O-、-SiR” 2 -, -PR”-, -S-, -C(=O)-, -C(=S)-, -C(=NR”)-, -C(=CR” 2 )-and any one of L1 to L8 below;
[0039]
[0040]
[0041] Among them, Z 1 To Z 40 are independently selected from any one of =CR"-, =N-; X 6 To X 11 Selected from -CR" 2 -、-NR”-、-O-、-SiR” 2 -, -PR”-, -S-, -As-, -Se-, -C(=O)-, -C(=S)-, -C(=NR”)-, -C(=CR” 2 )-; R" is selected from hydrogen, halogen, -OR', -OCOR', -NHCOR', -NR' 2 , R', halogen-substituted R', -SR', -PR' 2 , -AsR' 2 , -Se-; R' is any one of substituted or unsubstituted phenyl, thienyl, and C1-C5 alkyl. By making the L group any of the above, the selection diversity of the first self-assembled molecular material is increased. When L includes any one of a phosphorus atom, a sulfur atom, an arsenic atom, and a selenium atom, more coordination sites can be provided to passivate more interface defects of the light absorption layer, thereby enhancing the passivation effect of the first self-assembled molecular material on perovskite.
[0042] In one embodiment, the first self-assembling molecular material is selected from any one of SAM1 to SAM17:
[0043]
[0044]
[0045] SAM1 to SAM17 include at least one of phosphorus, sulfur, arsenic, and selenium atoms as coordinating atoms, and also include nitrogen or oxygen atoms that can coordinate with the lead of the perovskite. Compared with the self-assembled molecules in the prior art that passivate by combining with the lead of the perovskite through nitrogen or oxygen atoms, and the binding strength of phosphorus, sulfur, arsenic, and selenium atoms with the lead of the perovskite is stronger than that of nitrogen and oxygen atoms with the lead of the perovskite, any one of SAM1 to SAM17 can improve the passivation effect on the perovskite, thereby improving the photoelectric conversion efficiency and stability of the solar cell.
[0046] In one embodiment, a second self-assembled molecular material is further included, wherein the second self-assembled molecular material includes at least one of an oxygen atom and a nitrogen atom containing unbonded lone pairs of electrons. The self-assembled material formed by mixing the first self-assembled molecular material and the second self-assembled molecular material is used to passivate the light absorbing layer, which can achieve a better passivation effect and help improve the photoelectric conversion efficiency and stability of the solar cell. The perovskite cell has a larger open circuit voltage, short circuit current density and fill factor, a higher photoelectric conversion efficiency, and better stability.
[0047] In one embodiment, the second self-assembling molecular material is selected from any one of the following compounds M1 to M4:
[0048]
[0049] In order to solve the above technical problems, another technical solution adopted in the present application is: to provide a solar cell, comprising the self-assembly material described in any of the above items, wherein the self-assembly material combines with the lead vacancies in the light absorption layer to form a strong coordination bond, thereby achieving passivation of the low-coordinated lead of the perovskite, reducing defects on the interface of the light absorption layer, and making the solar cell have a higher photoelectric conversion efficiency and better stability.
[0050] In one embodiment, it includes a light absorbing layer and a passivation layer located on one side of the light absorbing layer, wherein the passivation layer includes the self-assembly material. The self-assembly material can be used as an independent passivation layer to passivate the low-coordinated lead vacancies in the light absorbing layer, reduce defects on the interface of the light absorbing layer, and enable the solar cell to have higher photoelectric conversion efficiency and better stability.
[0051] In one embodiment, it includes a light absorbing layer and a hole transport layer located on one side of the light absorbing layer, wherein the hole transport layer includes the self-assembled material. The self-assembled material can be used as a hole transport material to achieve hole transport while passivating the interface defects of the light absorbing layer, thereby reducing the film structure of the solar cell and reducing the thickness, so that the solar cell has a higher photoelectric conversion efficiency and better stability.
[0052] In one embodiment, the hole transport layer further comprises a metal oxide; optionally, the self-assembly material is attached to the surface of the metal oxide. That is, the hole transport layer comprises a mixed material of the self-assembly material and the metal oxide, and the self-assembly material can passivate the surface of the metal oxide while passivating the interface defects of the light absorption layer, so that the solar cell has a larger open circuit voltage, short circuit current density and fill factor, which is conducive to improving the photoelectric conversion efficiency and stability of the solar cell.
[0053] In one embodiment, the hole transport layer comprises a self-assembled material layer and a metal oxide layer which are stacked, wherein the self-assembled material layer comprises the self-assembled material, and the metal oxide layer comprises a metal oxide. The self-assembled material can passivate the surface of the metal oxide while passivating the interface defects of the light absorption layer, thereby improving the photoelectric conversion efficiency and stability of the solar cell.
[0054] In one embodiment, the self-assembly material layer has a thickness of 0.1 nm to 5 nm, a large specific surface area, a high utilization rate of coordinated atoms, and good self-assembly performance.
[0055] In one embodiment, the metal oxide includes at least one of nickel oxide, molybdenum oxide, and tungsten oxide; and / or the thickness of the metal oxide layer is 10nm-100nm, achieving a better hole transport effect. The self-assembled material provided in the present application can passivate the metal oxide provided above, which is beneficial to improving the photoelectric conversion efficiency and stability of solar cells.
[0056] In one embodiment, a light absorbing layer is included, wherein the light absorbing layer includes a perovskite material, wherein the chemical formula of the perovskite material is ABX 3 or A 2 CDX 6 , wherein A is at least one of MA, FA, and Cs, B is at least one of Pb and Sn, C is Ag+, and D is Bi 3+ , Sb 3+ 、In 3+ At least one of, X is at least one of Br, I, and provides a specific light absorption layer material. The self-assembled material provided in the present application can passivate the perovskite provided above, which is beneficial to improve the photoelectric conversion efficiency and stability of the perovskite solar cell.
[0057] In one embodiment, the band gap of the light absorption layer is 1.20eV-2.30eV, which can absorb a wider range of the solar spectrum; and / or the thickness of the light absorption layer is 200nm-1000nm, which is beneficial to reduce the transmittance of light, thereby increasing the light absorption rate, and at the same time helps to reduce the probability of electrons being recombined during the transmission process, and the solar cell has a higher photoelectric conversion efficiency.
[0058] In one embodiment, it further comprises an electron transport layer, a blocking layer, and a second electrode disposed on one side of the light absorbing layer, and a first electrode disposed on the other side of the light absorbing layer, wherein the blocking layer is located between the electron transport layer and the second electrode;
[0059] Optionally, the electron transport layer comprises [6,6]-phenyl-C 61 -Butyric acid methyl ester, [6,6]-phenyl-C71 - at least one of methyl butyrate, fullerene C60, fullerene C70, tin dioxide, zinc oxide, perylene imide materials, and naphthylimide materials, and / or the thickness of the electron transport layer is 5nm-100nm;
[0060] Optionally, the barrier layer includes 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline, SnO2, ZnO, CeO x At least one of the following, and / or the thickness of the barrier layer is 0.5nm-20nm;
[0061] Optionally, the second electrode comprises at least one of Ag, Cu, C, Au, Al, ITO, AZO, BZO, and IZO, and / or the thickness of the second electrode is 10 nm-1000 nm;
[0062] Optionally, the first electrode includes at least one of FTO, ITO, AZO, BZO, and IZO, and / or the thickness of the first electrode is 10 nm-1000 nm.
[0063] The light absorption layer absorbs photons from sunlight to generate excitation, which excites electrons in the valence band to generate photogenerated holes and electron pairs; free electrons are transmitted to the second electrode through the second transmission layer, and free holes are transmitted to the first electrode through the first transmission layer; free electrons are collected by the second electrode after passing through the second transmission layer, and free holes are collected by the first electrode after passing through the first transmission layer. In other words, by designing the first electrode, the first transmission layer, the light absorption layer, the second transmission layer, and the second electrode as described above, a potential difference is formed between the first electrode and the second electrode, and the solar cell and the external load can form a closed loop, forming a current in the loop.
[0064] To solve the above technical problems, another technical solution adopted by the present application is to provide an electrical device, comprising any of the above-mentioned solar cells. The electrical device has at least the same advantages as the solar cell.
[0065] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0067] Figure 1 It is a schematic diagram of the structure of a solar cell provided in an embodiment of the present application.
[0068] In the attached figure:
[0069] 100. Solar cell; 11. First electrode; 12. First transmission layer; 13. Light absorption layer; 14. Second transmission layer; 15. Second electrode; 16. Blocking layer. DETAILED DESCRIPTION
[0070] In order to make the purpose, technical solution and effect of the present application clearer and more specific, the following will describe the embodiments of the technical solution of the present application in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0071] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0072] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two), and similarly, "multiple groups" refers to more than two (including two groups), and "multiple pieces" refers to more than two (including two pieces), unless otherwise clearly and specifically defined.
[0073] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0074] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0075] Amounts, ratios and other numerical values are presented herein in a range format. It should be understood that such a range format is for convenience and brevity and should be flexibly interpreted to include not only the values explicitly specified as range limits, but also all individual values or sub-ranges encompassed within the range, as if each value and sub-range were explicitly specified.
[0076] If there is no special explanation, all steps of the present application can be performed sequentially, randomly, or in parallel, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially, or may be steps (a) and (b) performed simultaneously in parallel. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0077] With the rapid development of new energy technologies, solar cells have been widely used in military, aerospace, industry, commerce, agriculture, communications and other fields. Perovskite solar cells have gradually become a hot topic in the research of the new generation of solar cells due to their advantages such as high photoelectric conversion efficiency, simple manufacturing process, low production cost and material cost.
[0078] There are a large number of defects on the perovskite interface, which affect the photoelectric conversion efficiency and stability of perovskite solar cells. To improve the photoelectric conversion efficiency and stability of perovskite solar cells, self-assembly materials can be used to passivate the perovskite interface. Existing self-assembly materials contain three parts, namely, the end group (Ar), the carbon chain (L), and the head group (A). Among them, the end group contacts the perovskite interface, and the active functional groups on the end group are mainly alkoxy, aniline, etc. The oxygen and nitrogen atoms with lone pairs of electrons on the end group can passivate the low-coordinated lead vacancies to a certain extent, thereby improving the photoelectric conversion efficiency and stability of perovskite solar cells. However, the effect of the oxygen and nitrogen atoms with lone pairs of electrons on the lead vacancies is not strong, the degree of passivation is limited, and the improvement of the photoelectric conversion efficiency of perovskite solar cells is limited.
[0079] Based on this, the present application provides a self-assembly material, a solar cell and an electrical device to increase the interaction between the self-assembly material and the lead vacancies on the perovskite, increase the passivation effect of the self-assembly material on the perovskite interface, and thereby improve the photoelectric conversion efficiency and stability of the perovskite solar cell.
[0080] See also Figure 1 , Figure 1It is a schematic diagram of the structure of a solar cell provided in an embodiment of the present application.
[0081] The solar cell 100 includes a substrate layer (not shown), a first electrode 11, a first transmission layer 12, a light absorbing layer 13, a second transmission layer 14, and a second electrode 15 which are sequentially stacked. The solar cell 100 includes a self-assembly material.
[0082] When the solar cell is a trans structure, the first electrode 11 is an anode, the first transport layer 12 is a hole transport layer, the second transport layer 14 is an electron transport layer, and the second electrode 15 is a cathode. When the solar cell is a regular structure, the first electrode 11 is a cathode, the first transport layer 12 is an electron transport layer, the second transport layer 14 is a hole transport layer, and the second electrode 15 is an anode.
[0083] Now, taking a solar cell with an inverted structure as an example, the solar cell 100 is described in detail.
[0084] The light absorption layer 13 is used to absorb light and directly convert light energy into electrical energy through the photoelectric effect or the photochemical effect. The light absorption layer 13 includes a light-absorbing material with a photoelectric conversion function. The light-absorbing material absorbs photons of sunlight to generate excitation, and excites electrons in the valence band to generate photogenerated holes and electron pairs. Free electrons are transmitted to the second electrode 15 through the second transmission layer 14, and free holes are transmitted to the first electrode 11 through the first transmission layer 12. After passing through the second transmission layer 14, the free electrons are collected by the second electrode 15, and after passing through the first transmission layer 12, the free holes are collected by the first electrode 11. A potential difference is formed between the first electrode 11 and the second electrode 15, and the solar cell and the external load form a closed loop, and a current is formed in the loop.
[0085] In one embodiment, the material of the light absorbing layer 13 includes but is not limited to perovskite. The chemical formula of perovskite is ABX 3 or A 2 CDX 6 , wherein A is an inorganic cation and / or an organic cation, B is an inorganic cation and / or an organic cation, C is an inorganic cation and / or an organic cation, D is an inorganic cation and / or an organic cation, and X is an inorganic anion and / or an organic anion.
[0086] A is an inorganic cation, an organic cation, or a mixture of an inorganic cation and an organic cation. Optionally, A is a methylamino group (CH 3 NH 3 + )(MA + ), carboxamidino (HC(NH 2 ) 2 + )(FA + ), cesium ion (Cs +) at least one of.
[0087] B is an inorganic cation, or an organic cation, or a mixture of an inorganic cation and an organic cation. Optionally, B is a divalent metal ion Pb 2+ and Sn 2+ At least one of .
[0088] C is an inorganic cation, or an organic cation, or a mixture of an inorganic cation and an organic cation. Optionally, C is a monovalent metal ion Ag. + wait.
[0089] D is an inorganic cation, or an organic cation, or a mixture of an inorganic cation and an organic cation. Optionally, D is a trivalent metal ion bismuth cation Bi 3+ 、Antimony cation Sb 3+ 、Indium cation In 3+ At least one of .
[0090] X is an inorganic anion, an organic anion, or a mixture of an inorganic anion and an organic anion. Optionally, X is one or more of a halogen anion, and further optionally a bromide ion (Br - ), iodide ion (I - ) at least one of.
[0091] In one embodiment, the band gap of the light absorbing layer 13 is 1.20 eV-2.30 eV, which can absorb a wider range of the solar spectrum. At the same time, the energy level of the light absorbing layer 13 can match the energy levels of the hole transport layer and the electron transport layer.
[0092] In one embodiment, the thickness of the light absorbing layer 13 is 200nm-1000nm, which is beneficial to reduce the light transmission, thereby increasing the light absorption rate, and at the same time, it is beneficial to reduce the probability of electrons being recombined during the transmission process, and the solar cell has a higher photoelectric conversion efficiency.
[0093] The second transport layer 14 (electron transport layer) is disposed on one side of the light absorbing layer 13. The function of the second transport layer 14 (electron transport layer) is to efficiently transport the free electrons generated by the light absorbing layer 13 (perovskite layer), effectively block the passage of free holes, and form an ohmic contact with the interface of the light absorbing layer 13. The material of the electron transport layer is at least one of the following materials and their derivatives and materials obtained by doping or passivation. The electron transport material includes but is not limited to [6,6]-phenyl-C 61 -Methyl butyrate (PC 61 BM), [6,6]-phenyl-C 71 -Methyl butyrate (PC 71BM), fullerene C60 (C60), fullerene C70 (C70), tin dioxide (SnO2), zinc oxide (ZnO), perylene diimide (PDI) type materials, and naphthalene diimide (NDI) type materials.
[0094] In one embodiment, the thickness of the second transport layer 14 (electron transport layer) is 5 nm to 100 nm.
[0095] The second electrode 15 is arranged on the side of the second transmission layer 14 away from the light absorption layer 13. The second electrode 15 has the function of collecting free electrons. The second electrode 15 is usually an organic conductive material or an inorganic conductive material or a mixture of an organic conductive material and an inorganic conductive material. The organic conductive material is, for example, a conductive polymer, and the conductive polymer includes but is not limited to at least one of polyethylene dioxythiophene (PEDOT), polythiophene, and polyacetylene; the inorganic conductive material is, for example, but not limited to at least one of a transparent conductive oxide, a metal, and a carbon derivative, and the inorganic conductive material is specifically, for example, Ag, Cu, C, Au, Al, ITO (indium tin oxide), AZO (aluminum-doped zinc oxide), BZO (boron-doped zinc oxide), IZO (indium zinc oxide), etc.
[0096] In one embodiment, the thickness of the second electrode 15 is 10 nm-1000 nm.
[0097] In one embodiment, a blocking layer 16 is provided between the second transport layer 14 and the second electrode 15. The blocking layer 16 has a low valence band and can effectively block the transmission of holes and reduce the energy loss caused by charge recombination. Optionally, the material of the blocking layer 16 includes but is not limited to 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline (BCP), SnO 2 , ZnO, CeO x Optionally, the barrier layer 16 has a thickness of 0.5 nm to 20 nm.
[0098] The first transport layer 12 (hole transport layer) is disposed on one side of the light absorbing layer 13, and the first transport layer 12 and the second transport layer 14 are located on opposite sides of the light absorbing layer 13. The first transport layer 12 is used to transport holes to the corresponding first electrode 11 and prevent holes from diffusing in the opposite direction.
[0099] In one embodiment, the first transport layer 12 (hole transport layer) includes but is not limited to at least one of 2,2',7,7'-tetrakis(N,N-p-methoxyanilino)-9,9'-spirobifluorene (Spiro-OMeTAD), methoxytriphenylamine-fluoroformamidine, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], poly(3,4-ethylenedioxythiophene), polystyrene sulfonic acid, poly-3-hexylthiophene, triphenylamine with triptycene as the core, 3,4-ethylenedioxythiophene-methoxytriphenylamine, N-(4-anilino)carbazole-spirobifluorene, polythiophene, phosphate-based monomers, carbazole-based monomers, sulfonic acid-based monomers, triphenylamine-based monomers, aromatic monomers, metal oxides and cuprous thiocyanate, wherein the metal element in the metal oxide selected in the hole transport material includes at least one of Ni, Mo and Cu.
[0100] In one embodiment, a passivation layer is provided between the light absorbing layer 13 and the first transport layer 12 (hole transport layer), and the passivation layer is used for defects on the interface of the light absorbing layer 13 and the hole transport layer to improve the performance of the perovskite solar cell. Optionally, the material of the passivation layer is a self-assembly material. The existing self-assembly material comprises three parts, namely, an end group (Ar), a carbon chain (L), and a head group (A), wherein the end group is in contact with the perovskite interface of the light absorbing layer 13, and the active functional groups on the end group are mainly alkoxy, aniline, etc., and the oxygen and nitrogen atoms of the lone pair of electrons contained in the end group can passivate the low-coordinated lead to a certain extent, thereby realizing the improvement of the photoelectric conversion efficiency and stability of the perovskite solar cell. However, the effect of the oxygen and nitrogen atoms of the lone pair of electrons contained in the lead vacancy is not strong, the degree of passivation is limited, and the photoelectric conversion efficiency of the perovskite solar cell is limited.
[0101] It should be noted that the material of the first transmission layer 12 (hole transmission layer) can be a self-assembly material, which can realize the hole transmission function while realizing the passivation of the perovskite interface of the light absorption layer 13; at this time, it can be selected whether to omit the passivation layer between the light absorption layer 13 and the first transmission layer 12. However, the oxygen and nitrogen atoms of the lone pair electrons contained in the existing self-assembly material do not have a strong effect on the lead vacancies, and the degree of passivation is limited.
[0102] The first electrode 11 is disposed on the side of the first transport layer 12 (hole transport layer) away from the light absorption layer 13. The first electrode 11 has the function of collecting free holes. The first electrode 11 is usually a transparent electrode. The first electrode 11 includes but is not limited to FTO (fluorine-doped SnO 2 At least one of ITO (indium tin oxide transparent conductive glass), AZO (aluminum doped zinc oxide transparent conductive glass), BZO (boron doped zinc oxide transparent conductive glass), and IZO (indium zinc oxide transparent conductive glass).
[0103] In one embodiment, the thickness of the first electrode 11 is 10 nm-1000 nm.
[0104] The base layer is a transparent base layer. The material of the base layer includes glass and / or polymer; optionally, the polymer includes one or more of polyvinyl alcohol (PVA), polyester (PET), polyimide (PI), polyethylene naphthalate (PEN) and polydimethylsiloxane (PDMS). It should be noted that the base layer is an optional structure; that is, in some embodiments, the base layer may not be provided.
[0105] The self-assembly material provided in the embodiment of the present application includes a first self-assembly molecular material, the structural formula of the first self-assembly molecular material is Self-assembly is the phenomenon that the constituent elements of a system gather and organize into regular structures without the intervention of external human forces.
[0106] Wherein, Ar represents an aromatic group, Ar includes at least one coordinating atom, the coordinating atom includes an unbonded lone pair of electrons, and the coordinating atom includes one or more of a phosphorus atom, an arsenic atom, a sulfur atom, and a selenium atom. L includes one or more of a carbon-containing group, a nitrogen-containing group, an oxygen-containing group, a silicon-containing group, a phosphorus-containing group, and a sulfur-containing group, and the value of n is 0-10. A includes a hydrophilic group.
[0107] The Ar group of the first self-assembling molecular material is in contact with the light absorbing layer 13 of the solar cell 100, and the light absorbing layer 13 includes perovskite, so as to passivate and improve the surface defects of the light absorbing layer 13. By using one or more of phosphorus atoms, arsenic atoms, sulfur atoms, and selenium atoms as coordination atoms in the Ar group, the atomic radius of the coordination atoms is large, and the unbonded lone pair of electrons in the coordination atoms can be combined with the low-coordinated lead vacancies in the light absorbing layer to form a strong coordination bond, so as to passivate the low-coordinated lead of the perovskite, reduce the defects on the perovskite interface, and make the solar cell 100 have a higher photoelectric conversion efficiency and better stability. The use of one or more of phosphorus atoms, arsenic atoms, sulfur atoms, and selenium atoms as coordination atoms in the Ar group increases the diversity of the first self-assembling molecular material, and the range of material selection for passivating the lead vacancies in the perovskite using the self-assembling material is wider.
[0108] In the prior art, oxygen atoms or nitrogen atoms are used to passivate the low-coordinated lead of the perovskite. The embodiment of the present application uses one of phosphorus atoms, arsenic atoms, sulfur atoms, and selenium atoms to passivate the low-coordinated lead of the perovskite. The binding strength between phosphorus atoms and lead vacancies is stronger than the binding strength between oxygen atoms and lead vacancies, and is stronger than the binding strength between nitrogen atoms and lead vacancies. The binding strength between arsenic atoms and lead vacancies is stronger than the binding strength between oxygen atoms and lead vacancies, and is stronger than the binding strength between nitrogen atoms and lead vacancies. The binding strength between sulfur atoms and lead vacancies is stronger than the binding strength between oxygen atoms and lead vacancies, and is stronger than the binding strength between nitrogen atoms and lead vacancies. The binding strength between selenium atoms and lead vacancies is stronger than the binding strength between oxygen atoms and lead vacancies, and is stronger than the binding strength between nitrogen atoms and lead vacancies. Therefore, using one of phosphorus atoms, arsenic atoms, sulfur atoms, and selenium atoms to passivate the low-coordinated lead of the perovskite can achieve a better passivation effect than using oxygen atoms or nitrogen atoms to passivate the low-coordinated lead of the perovskite, thereby improving the photoelectric conversion efficiency and stability of the solar cell 100.
[0109] By designing the A group of the first self-assembly molecular material as a hydrophilic group, the A group is anchored to the film layer on the side of the light absorbing layer 13 away from the second electrode 15, and is evenly laid out in an array, that is, it is orderly arranged into a self-assembled thin film on the film layer on the side of the light absorbing layer 13 away from the second electrode 15 to achieve self-assembly; at the same time, the A group will also passivate the film layer on the side of the light absorbing layer 13 away from the second electrode 15, passivate the defects on the surface of the film layer on the side of the light absorbing layer 13 away from the second electrode 15, which is beneficial to improve the photoelectric conversion efficiency and stability of the solar cell 100.
[0110] Specifically, when the hole transport layer of the solar cell 100 includes the above-mentioned self-assembly material provided in the embodiment of the present application, the A group of the first self-assembly molecular material is in contact with the first electrode 11 (at this time, the hole transport layer only includes the self-assembly material), or the A group of the first self-assembly molecular material is in contact with the metal oxide of the hole transport layer (at this time, the hole transport layer includes the metal oxide and the self-assembly material attached to the surface of the metal oxide, or the hole transport layer includes a stacked metal oxide layer and a self-assembly material layer); when the passivation layer of the solar cell 100 (the passivation layer is arranged between the light absorption layer 13 and the hole transport layer) includes the above-mentioned self-assembly material, the A group of the first self-assembly molecular material is in contact with the hole transport layer (at this time, the material of the hole transport layer can be the material in the prior art or the material of the hole transport layer includes the self-assembly material provided in the embodiment of the present application).
[0111] In one embodiment, Ar includes two or more of the above-mentioned coordination atoms, which can provide more coordination sites to passivate more interface defects and enhance the passivation effect of the first self-assembled molecular material on perovskite.
[0112] In one embodiment, Ar is any one of the following Ar1 to Ar12:
[0113]
[0114] Among them, X 1 To X 5 Selected from -CR" 2 -、-NR”-、-O-、-SiR” 2 -, -PR”-, -S-, -As-, -Se-, -C(=O)-, -C(=S)-, -C(=NR”)-, -C(=CR” 2 )-, the value of m is 1-3; R 1 To R 143 and R" are independently selected from hydrogen, halogen, -OR', -OCOR', -NHCOR', -NR' 2 , R', halogen-substituted R', -SR', -PR' 2 , -AsR' 2 , -Se-; R' is any one of substituted or unsubstituted phenyl, thienyl, and C1-C5 alkyl. By making Ar any one of Ar1 to Ar12, and R 1 To R 143 and X 1 To X 5 Providing the above-mentioned multiple groups increases the selection diversity of the first self-assembling molecular material, can enhance the affinity of the first self-assembling molecular material with the light absorbing material precursor solution, and at the same time, is conducive to uniform coating over a large area and improves preparation efficiency.
[0115] Optionally, when Ar is Ar1, R 1 To R 8 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar2, R 9 To R 18 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar3, R 19 To R 30 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar4, R 31 To R 44 At least one of them is selected from -PR' 2、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar5, R 45 To R 60 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar6, R 61 To R 78 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar10, and X 1 When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 127 To R 134 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar11, and X 2 To X 3 When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 135 To R 138 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar12, and X 4 To X 5 When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 139 To R 143 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 By selecting the groups in Ar1 to Ar12 as above, Ar includes at least one phosphorus atom coordination atom, one sulfur atom coordination atom, one arsenic atom coordination atom, or one selenium atom coordination atom, which improves the passivation ability of lead vacancies in perovskite compared with the prior art.
[0116] Optionally, when Ar is Ar1, R 1 To R 8 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar2, R 9 To R 18 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar3, R 19 To R30 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar4, R 31 To R 44 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar5, R 45 To R 60 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar6, R 61 To R 78 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar7, R 79 To R 92 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar8, R 93 To R 108 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar9, R 109 To R 126 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar10 and X 1 When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 127 To R 134 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; or when Ar is Ar10 and X 1 When it contains one of the elements phosphorus, sulfur, arsenic, and selenium, R 127 To R 134 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar11 and X 2 To X 3When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 135 To R 138 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; or when Ar is Ar11 and X 2 To X 3 When it contains one of the elements phosphorus, sulfur, arsenic, and selenium, R 135 To R 138 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; and / or, when Ar is Ar12 and X 4 To X 5 When the group does not contain phosphorus, sulfur, arsenic, or selenium, R 139 To R 143 At least two of them are selected from -PR' 2 、-SR'、-AsR' 2 , -Se-; or when Ar is Ar12 and X 4 To X 5 When it contains one of the elements phosphorus, sulfur, arsenic, and selenium, R 139 To R 143 At least one of them is selected from -PR' 2 、-SR'、-AsR' 2 By selecting the groups in Ar1 to Ar12 as above, Ar includes at least two coordination atoms among phosphorus, sulfur, selenium and arsenic, which can provide more coordination sites to passivate more interface defects of the light absorption layer, and further enhance the passivation effect of the first self-assembled molecular material on perovskite.
[0117] Optionally, when Ar is Ar1, R 1 To R 8 and / or, when Ar is Ar2, R 9 To R 18 and / or, when Ar is Ar3, R 19 To R 30 and / or, when Ar is Ar4, R 31 To R 44 and / or, when Ar is Ar5, R 45 To R 60 and / or, when Ar is Ar6, R 61 To R 78 and / or, when Ar is Ar7, R 79To R 92 and / or, when Ar is Ar8, R 93 To R 108 and / or, when Ar is Ar9, R 109 To R 126 and / or, when Ar is Ar10, R 127 To R 134 and / or, when Ar is Ar11, X 2 To X 3 The substituents in R are the same, 135 To R 138 and / or, when Ar is Ar12, X 4 To X 5 The substituents in R are the same, 139 To R 143 The substituents in the catalyst are the same, which simplifies the preparation process of the material and reduces the preparation cost.
[0118] In one embodiment, A includes a hydrophilic group, and the hydrophilic group includes one or more oxyacid groups, and the oxyacid groups are anchored to the film layer on the side of the light absorbing layer 13 away from the second electrode 15 to achieve self-assembly. The selection of oxyacid groups as anchoring groups can reduce the difficulty of the synthesis process. Specifically, the oxyacid groups can be orderly arranged into a self-assembled molecular film on the first electrode 11 (in this case, the material of the hole transport layer can only include self-assembled materials); or they can be in contact with the metal oxide hole transport layer, and orderly arranged into a self-assembled molecular film on the metal oxide hole transport layer, while passivating the surface defects of the metal oxide hole transport layer (in this case, the hole transport layer includes a metal oxide and a self-assembled material attached to the surface of the metal oxide, or the hole transport layer includes a stacked metal oxide layer and a self-assembled material layer).
[0119] Optionally, the oxygen acid group includes -COOH, a salt corresponding to -COOH, -PO(OH) 2 、-PO(OH) 2 The corresponding salt, -PHO(OH), the corresponding salt of -PHO(OH), -SO 2 (OH), -SO 2 (OH) corresponding salt, -B(OH) 2 、-B(OH) 2 By making the oxygen acid group any of the above, the selection diversity of the first self-assembly molecular material is increased, the affinity of the anchoring group and the film layer on the side of the light absorbing layer away from the second electrode can be improved, and the anchoring strength can be enhanced.
[0120] In one embodiment, L is -CR" 2-、-NR”-、-O-、-SiR” 2 -, -PR”-, -S-, -C(=O)-, -C(=S)-, -C(=NR”)-, -C(=CR” 2 )-and at least one of the following L1 to L8.
[0121]
[0122]
[0123] Among them, Z 1 To Z 40 are independently selected from any one of =CR"-, =N-; X 6 To X 11 Selected from -CR" 2 -、-NR”-、-O-、-SiR” 2 -, -PR”-, -S-, -As-, -Se-, -C(=O)-, -C(=S)-, -C(=NR”)-, -C(=CR” 2 )-; R" is selected from hydrogen, halogen, -OR', -OCOR', -NHCOR', -NR' 2 , R', halogen-substituted R', -SR', -PR' 2 , -AsR' 2 , -Se-; R' is any one of substituted or unsubstituted phenyl, thienyl, and C1-C5 alkyl. By making the L group any of the above, the selection diversity of the first self-assembled molecular material is increased. When L includes any one of phosphorus atoms, sulfur atoms, arsenic atoms, and selenium atoms, more coordination sites can be provided to passivate more interface defects of the light absorption layer 13, thereby enhancing the passivation effect of the first self-assembled molecular material on perovskite.
[0124] In one embodiment, the first self-assembling molecular material is selected from any one of SAM1 to SAM17:
[0125]
[0126]
[0127] The first self-assembling molecular material is selected from any one of SAM1 to SAM17. SAM1 to SAM17 are composed of one of the above-mentioned multiple groups of Ar, one of the above-mentioned multiple groups of L, and one of the above-mentioned multiple groups of A. SAM1 to SAM17 include at least one coordinating atom of phosphorus atom, sulfur atom, arsenic atom, and selenium atom, and also include nitrogen atom or oxygen atom that can coordinate with the lead vacancy of perovskite. Compared with the self-assembling molecules in the prior art, the lead vacancy of perovskite is combined and passivated by nitrogen atom or oxygen atom, and the binding strength of phosphorus atom, sulfur atom, arsenic atom, and selenium atom with the lead vacancy of perovskite is stronger than the binding strength of nitrogen atom and oxygen atom with the lead vacancy of perovskite. By using any one of SAM1 to SAM17, the passivation effect on perovskite can be improved, thereby improving the photoelectric conversion efficiency and stability of the solar cell 100.
[0128] The present application also provides a method for preparing SAM1, which is specifically:
[0129] Step 1: Compound 1 (1 mmol), compound 2 (8 mL), 50% potassium hydroxide aqueous solution (KOH (aq), 5 mL), and tetrabutylammonium bromide (TBAB, 5% mmol) were mixed, heated at 70 degrees Celsius for 20 hours under nitrogen protection, and separated by silica gel chromatography column to obtain compound 3 with a yield of about 83%. 1 H NMR (400 MHz, CDCl 3 )δ7.73(d,J=7.2Hz,2H),7.28(s,2H),7.06(d,J=7.2Hz,2H),4.18-4.15(m,2H),3.54-3.51(m,2H),2.45(s,6H),1.83-1.74(m,4H).
[0130] Step 2: Compound 3 (0.8 mmol), triethyl phosphite (P(OEt) 3 , 10 mL) were mixed, heated at 180 degrees Celsius for 12 hours under nitrogen protection, and triethyl phosphite was removed by reduced pressure distillation. The crude product was mixed with tributylsilyl bromide (TMSBr, 0.72 mmol) and 1,4-dioxane (5 mL), stirred at room temperature for 20 hours under nitrogen protection, and the solvent was removed. Methanol (5 mL) was added and stirred for 12 hours, and deionized water (1 mL) was added to precipitate solid powder. SAM1 was obtained after filtration and washing. The yield was about 45%. 1 H NMR (400 MHz, DMSO-d 6)δ7.73(d,J=7.2Hz,2H),7.28(s,2H),7.06(d,J=7.2Hz,2H),4.18-4.15(m,2H),2.45(s,6H),1.83-1.74(m,4H),1.26-1.22(m,2H).
[0131]
[0132] The present application also provides a method for preparing SAM2, specifically:
[0133] Step 1: Compound 1 (1 mmol), compound 4 (1.2 mmol), cuprous iodide (CuI, 5% mmol), potassium hydroxide (KOH, 1.2 mmol), and toluene (10 mmol) were mixed, heated at 110 degrees Celsius for 20 hours under nitrogen protection, and separated by silica gel chromatography to obtain compound 5 with a yield of about 76%. 1 H NMR (400 MHz, CDCl 3 )δ7.83(d,J=7.2Hz,2H),7.48(d,J=7.2Hz,4H),7.28(d,J=7.2Hz,4H),7.06(d,J= 7.2Hz,2H),4.18-4.15(m,2H),3.65-3.62(m,2H),3.06-3.03(m,2H),2.45(s,6H).
[0134] Step 2: Compound 5 (0.7 mmol), triethyl phosphite (P(OEt) 3 , 10mL) were mixed, heated at 180 degrees Celsius for 12 hours under nitrogen protection, and triethyl phosphite was removed by reduced pressure distillation. The crude product was mixed with tributylsilyl bromide (TMSBr, 0.72mmol) and 1,4-dioxane (5mL), stirred at room temperature for 20 hours under nitrogen protection, and the solvent was removed. Methanol (5mL) was added and stirred for 12 hours, and deionized water (1mL) was added to precipitate solid powder. SAM2 was obtained after filtration and washing. The yield was 35%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.87(d,J=7.2Hz,2H),7.49(d,J=7.2Hz,4H),7.28(d,J=7.2Hz,2H),7.06(d,J= 7.2Hz,2H),2.82-2.80(m,2H),3.06-3.03(m,2H),2.45(s,6H),2.03-1.99(m,2H).
[0135]
[0136] The present application also provides a method for preparing SAM3, specifically:
[0137] Step 1: Compound 6 (1 mmol), compound 2 (8 mL), 50% potassium hydroxide aqueous solution (KOH (aq), 5 mL), and tetrabutylammonium bromide (TBAB, 5% mmol) were mixed, heated at 70 degrees Celsius for 20 hours under nitrogen protection, and separated by silica gel chromatography column to obtain compound 7 with a yield of about 79%. 1 H NMR (400 MHz, CDCl -3 )δ8.97(d,J=7.2Hz,2H),8.12(d,J=7.2Hz,2H),7.59(d,J=7.2Hz,4H),7.20(d,J=7.2Hz,2H ),4.18-4.15(m,2H),3.55-3.52(m,2H),2.45(s,6H),1.82-1.79(m,2H),1.75-1.73(m,2H).
[0138] Step 2: Compound 7 (0.8 mmol), triethyl phosphite (P(OEt) 3 , 10mL) were mixed, heated at 180 degrees Celsius for 12 hours under nitrogen protection, and triethyl phosphite was removed by reduced pressure distillation. The crude product was mixed with tributylsilyl bromide (TMSBr, 0.72mmol) and 1,4-dioxane (5mL), stirred at room temperature for 20 hours under nitrogen protection, and the solvent was removed. Methanol (5mL) was added and stirred for 12 hours, and deionized water (1mL) was added to precipitate solid powder. SAM3 was obtained after filtration and washing. The yield was about 43%. 1 H NMR (400 MHz, DMSO-d 6 )δ8.97(d,J=7.2Hz,2H),8.12(d,J=7.2Hz,2H),7.59(d,J=7.2Hz,4H),7.20(d,J=7.2Hz,2H ),4.18-4.15(m,2H),2.45(s,6H),1.75-1.73(m,2H),1.67-1.65(m,2H),1.27-1.25(m,2H).
[0139]
[0140] The present application also provides a method for preparing SAM4, specifically:
[0141] Step 1: Compound 8 (1 mmol), compound 4 (1.2 mmol), sodium tert-butoxide (t-BuONa, 1.2 mmol), tri-tert-butylphosphine (t-Bu 3 P, 10% mmol), tris(dibenzylideneacetone)dipalladium(0) (Pd 2 dba 3 , 5% mmol), toluene (10 mL), heated at 110 degrees Celsius for 12 hours under nitrogen protection, and after the reaction, the solvent was removed and purified by silica gel chromatography to obtain compound 9 with a yield of about 85%. 1 H NMR (400 MHz, CDCl -3 )δ7.49(d,J=7.2Hz,4H),7.19(d,J=7.2Hz,2H),7.08-7.03(m,6H),3.65-3.62(m,2H),2.95-2.92(m,2H),2.38(s,6H).
[0142] Step 2: Compound 9 (0.8 mmol), triethyl phosphite (P(OEt) 3 , 10mL) were mixed, heated at 180 degrees Celsius for 12 hours under nitrogen protection, and triethyl phosphite was removed by reduced pressure distillation. The crude product was mixed with tributylsilyl bromide (TMSBr, 0.72mmol) and 1,4-dioxane (5mL), stirred at room temperature for 20 hours under nitrogen protection, and the solvent was removed. Methanol (5mL) was added and stirred for 12 hours, and deionized water (1mL) was added to precipitate solid powder. SAM4 was obtained after filtration and washing. The yield was about 51%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.49(d,J=7.2Hz,4H),7.19(d,J=7.2Hz,2H),7.08-7.03(m,6H),2.71-2.68(m,2H),2.38(s,6H),2.03-2.00(m,2H).
[0143]
[0144] The present application also provides a method for preparing SAM5, specifically:
[0145] Step 1: Compound 10 (1 mmol) and compound 11 (2.2 mmol) were dissolved in N,N-dimethylformamide (DMF, 5 mL), potassium hydroxide (KOH, 4.8 mmol) was added, and the mixture was heated and stirred at 110 degrees Celsius for 12 hours under nitrogen protection. After the reaction, dilute hydrochloric acid was added to precipitate a solid precipitate, which was filtered and washed to obtain SAM5 with a yield of about 23%.1 HNMR (400 MHz, DMSO-d 6 )δ7.88(d,J=7.2Hz,2H),7.47-7.36(m,14H),7.15-7.12(m,10),4.18-4.15(m,2H),1.76-1.63(m,4H),1.26-1.23(m,2H).
[0146]
[0147] The present application also provides a method for preparing SAM6, specifically:
[0148] Step 1: Compound 12 (0.8 mmol), triethyl phosphite (P(OEt) 3 , 10 mL) were mixed, heated at 180 degrees Celsius for 12 hours under nitrogen protection, and triethyl phosphite was removed by reduced pressure distillation. The crude product was mixed with tributylsilyl bromide (TMSBr, 0.72 mmol) and 1,4-dioxane (5 mL), stirred at room temperature for 20 hours under nitrogen protection, and the solvent was removed. Methanol (5 mL) was added and stirred for 12 hours, and deionized water (1 mL) was added to precipitate solid powder. After filtration and washing, compound 13 was obtained with a yield of about 51%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.38(d,J=7.2Hz,4H),7.18(d,J=7.2Hz,2H),7.07-7.03(m,6H),4.18-4.15(m,2H),2.71-2.68(m,2H),2.03-2.00(m,2H).
[0149] Step 2: Compound 13 (1 mmol) and compound 11 (2.2 mmol) were dissolved in N,N-dimethylformamide (DMF, 5 mL), potassium hydroxide (KOH, 4.8 mmol) was added, and the mixture was heated and stirred at 110 degrees Celsius for 12 hours under nitrogen protection. After the reaction, dilute hydrochloric acid was added to precipitate a solid precipitate, which was filtered and washed to obtain SAM6 with a yield of about 36%. 1 HNMR (400 MHz, DMSO-d 6 )δ7.47-7.44(m,12H),7.20-7.03(m,20H),2.71-2.68(m,2H),2.03-2.00(m,2H).
[0150]
[0151] The present application also provides a method for preparing SAM7, specifically:
[0152] Step 1: Compound 14 (1 mmol) and compound 15 (1.1 mmol) were dissolved in N,N-dimethylformamide (DMF, 5 mL), potassium hydroxide (KOH, 3.6 mmol) was added, and heated at 110 degrees Celsius for 12 hours under nitrogen protection. After the reaction, dilute hydrochloric acid was added to acidify to obtain solid powder SAM7 with a yield of 45%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.40-7.37(m,4H),7.22-7.15(m,4H),7.05(d,J=7.2Hz,4H),2.82-2.79(m,2H),2.03-2.00(m,2H).
[0153]
[0154] The present application also provides a method for preparing SAM8, specifically:
[0155] Step 1: Compound 16 (1 mmol), compound 17 (5 mmol), palladium acetate (Pd(OAc) 2 , 10%mmol), 1,2-bis(diphenylphosphino)ethanenickel chloride (Ni(dppe)Cl 2 , 10% mmol), bis(diphenylphosphinothiocene) (dppf, 10% mmol), potassium monohydrogen phosphate (K 2 HPO 4 , 2mmol), zinc powder (Zn, 2.5mmol), 4A molecular sieve (4A MS, 100mg) were dissolved in N,N-dimethylacetamide (DMAc, 10mL), heated at 100 degrees Celsius for 12 hours under nitrogen protection, and diluted hydrochloric acid was added after the reaction to acidify to obtain solid powder compound 18 with a yield of 88%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.16-7.10(m,4H),6.83(s,2H),2.45(s,6H).
[0156] Step 2: Compound 18 (1 mmol), compound 2 (8 mL), 50% potassium hydroxide aqueous solution (KOH (aq), 5 mL), and tetrabutylammonium bromide (TBAB, 5% mmol) were mixed, heated at 70 degrees Celsius for 20 hours under nitrogen protection, and separated by silica gel chromatography column to obtain compound 19 with a yield of about 78%. 1 H NMR (400 MHz, CDCl 3)δ7.19-7.07(m,4H),6.83(s,2H),3.95-3.90(m,2H),3.54-3.50(m,2H),2.45(s,6H),1.83-1.80(m,2H),1.50-1.47(m,2H).
[0157] Step 3: Compound 19 (0.8 mmol), triethyl phosphite (P(OEt) 3 , 10 mL) were mixed, heated at 180 degrees Celsius for 12 hours under nitrogen protection, and triethyl phosphite was removed by reduced pressure distillation. The crude product was mixed with tributylsilyl bromide (TMSBr, 0.72 mmol) and 1,4-dioxane (5 mL), stirred at room temperature for 20 hours under nitrogen protection, and the solvent was removed. Methanol (5 mL) was added and stirred for 12 hours, and deionized water (1 mL) was added to precipitate solid powder. SAM8 was obtained after filtration and washing, with a yield of about 58%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.16-7.10(m,4H),6.83(s,2H),3.96-3.91(m,2H),2.45(s,6H),1.68-1.65(m,2H),1.51-1.47(m,2H),1.28-1.25(m,2H).
[0158]
[0159] The present application also provides a method for preparing SAM9, specifically:
[0160] Step 1: Compound 20 (1 mmol), compound 2 (8 mL), 50% potassium hydroxide aqueous solution (KOH (aq), 5 mL), and tetrabutylammonium bromide (TBAB, 5% mmol) were mixed, heated at 70 degrees Celsius for 20 hours under nitrogen protection, and separated by silica gel chromatography column to obtain compound 21 with a yield of about 70%. 1 H NMR (400 MHz, CDCl 3 )δ6.75(s,2H),4.18-4.14(m,2H),3.54-3.50(m,2H),2.37(s,6H),1.83-1.80(m,2H),1.76-1.72(m,2H).
[0161] Step 2: Compound 21 (0.8 mmol), triethyl phosphite (P(OEt) 3, 10mL) were mixed, heated at 180 degrees Celsius for 12 hours under nitrogen protection, and triethyl phosphite was removed by reduced pressure distillation. The crude product was mixed with tributylsilyl bromide (TMSBr, 0.72mmol) and 1,4-dioxane (5mL), stirred at room temperature for 20 hours under nitrogen protection, and the solvent was removed. Methanol (5mL) was added and stirred for 12 hours, and deionized water (1mL) was added to precipitate solid powder. SAM9 was obtained after filtration and washing, with a yield of about 59%. 1 H NMR (400 MHz, DMSO-d 6 )δ6.78(s,2H),4.20-4.16(m,2H),2.39(s,6H),1.74-1.65(m,4H),1.28-1.25(m,2H).
[0162]
[0163] The present application also provides a method for preparing SAM10, specifically:
[0164] Step 1: Compound 22 (0.8 mmol), triethyl phosphite (P(OEt) 3 , 10mL) were mixed, heated at 180 degrees Celsius for 12 hours under nitrogen protection, and triethyl phosphite was removed by reduced pressure distillation. The crude product was mixed with tributylsilyl bromide (TMSBr, 0.72mmol) and 1,4-dioxane (5mL), stirred at room temperature for 20 hours under nitrogen protection, and the solvent was removed. Methanol (5mL) was added and stirred for 12 hours, and deionized water (1mL) was added to precipitate solid powder. SAM10 was obtained after filtration and washing, with a yield of about 47%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.26(s,2H),4.05-4.02(m,2H),2.53(s,6H),2.33(s,3H),1.97-1.94(m,2H),1.66-1.63(m,2H).
[0165]
[0166] The present application also provides a method for preparing SAM11, which is as follows:
[0167] Step 1: Compound 23 (1 mmol) was dissolved in tetrahydrofuran (THF, 10 mL), the temperature was lowered to -78 degrees Celsius under nitrogen protection, butyl lithium solution (2.5 M hexane solution, 1.2 mmol) was slowly added dropwise, and triisopropyl borate (TPB, 1.3 mmol) was added dropwise after stirring at low temperature for 2 hours. After transferring to room temperature and stirring for 12 hours, it was purified by silica gel chromatography to obtain SAM11 with a yield of 36%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.71(d,J=7.5Hz,2H),7.49(d,J=7.5Hz,4H),7.18(d,J=7.5Hz,2H),7.08(d,J=7.5Hz,4H),2.38(s,6H).
[0168]
[0169] The present application also provides a method for preparing SAM12, specifically:
[0170] Step 1: Compound 24 (1 mmol), compound 25 (1.1 mmol), tetrakis(triphenylphosphine palladium (0)), potassium carbonate aqueous solution (2 M, 5 mL), and toluene (10 mL) were mixed, and heated at 110 degrees Celsius for 48 hours under nitrogen protection. The product compound 26 was separated by silica gel chromatography column with a yield of 73%. 1 H NMR (400 MHz, DMSO-d 6 )δ8.42(d,J=7.5Hz,1H),7.97(d,J=7.5Hz,1H),7.55(d,J=7.5Hz,2H),7.49(d,J=7.5Hz,4H),7 .18(d,J=7.5Hz,2H),7.08(d,J=7.5Hz,4H),4.29-4.26(m,2H),2.38(s,6H),1.30-1.26(m,3H).
[0171] Step 2: Compound 26 (1 mmol) was dissolved in tetrahydrofuran (THF, 10 mL), and an aqueous sodium hydroxide solution (NaOH aq, 2 M, 10 mL) was added. After heating at 75 °C for 20 h, dilute hydrochloric acid was added for acidification. The precipitate was filtered and washed to give the product SAM12 with a yield of 89%. 1H NMR (400 MHz, DMSO-d6) δ12.75 (s, 1H), 8.58 (d, J = 7.5 Hz, 1H), 8.07 (d, J = 7.5 Hz, 1H), 7.55 (d, J = 7.5 Hz, 2H), 7.49 (d, J = 7.5 Hz, 4H), 7.18 (d, J = 7.5 Hz, 2H), 7.08 (d, J = 7.5 Hz, 4H), 2.38 (s, 6H).
[0172]
[0173] The present application also provides a method for preparing SAM13, specifically:
[0174] Step 1: Compound 24 (1 mmol), compound 27 (1.1 mmol), tetrakis(triphenylphosphine palladium (0)), potassium carbonate aqueous solution (2 M, 5 mL), and toluene (10 mL) were mixed, and heated at 110 degrees Celsius for 48 hours under nitrogen protection. The product compound 28 was separated by silica gel chromatography column with a yield of 75%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.98(d,J=7.5Hz,1H),7.84(d,J=7.5Hz,1H),7.49(d,J=7.5Hz,4H),7.37(d,J=7.5Hz,2H),7 .08(d,J=7.5Hz,4H),6.99(d,J=7.5Hz,2H),4.35-4.29(m,2H),2.38(s,6H),1.34-1.29(m,3H).
[0175] Step 2: Compound 28 (1 mmol) was dissolved in tetrahydrofuran (THF, 10 mL), and sodium hydroxide aqueous solution (NaOH aq, 2 M, 10 mL) was added. After heating at 75 °C for 20 h, dilute hydrochloric acid was added to acidify, and the precipitate was filtered and washed to obtain the product SAM13 with a yield of 79%. 1 H NMR (400 MHz, DMSO-d 6)δ13.40(s,1H),8.03-7.98(m,2H),7.49(d,J=7.5Hz,4H),7.37(d,J=7.5Hz,2H),7.08(d,J=7.5Hz,4H),6.99(d,J=7.5Hz,2H),2.38(s,6H).
[0176]
[0177] The present application also provides a method for preparing SAM14, specifically:
[0178] Step 1: Compound 8 (1 mmol), compound 29 (1.2 mmol), sodium tert-butoxide (t-BuONa, 1.2 mmol), tri-tert-butylphosphine (10% mmol), tris(dibenzylideneacetone)dipalladium(0) (Pd 2 dba 3 , 5% mmol), toluene (10 mL), heated and stirred at 110 degrees Celsius for 12 hours under nitrogen protection, and after the reaction, the solvent was removed and purified by silica gel chromatography to obtain compound 30 with a yield of 61%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.48(d,J=7.5Hz,4H),7.29-7.23(m,1H),7.08(d,J=7.5Hz,4H),6.88-6.82(m,1H),3.63-3.60(m,2H),2.93-2.90(m,2H),2.38(s,6H).
[0179] Step 2: Compound 30 (0.8 mmol), triethyl phosphite (P(OEt) 3 , 10 mL) were mixed, heated at 180 degrees Celsius for 12 hours under nitrogen protection, and triethyl phosphite was removed by reduced pressure distillation. The crude product was mixed with tributylsilyl bromide (TMSBr, 0.72 mmol) and 1,4-dioxane (5 mL), stirred at room temperature for 20 hours under nitrogen protection, and the solvent was removed. Methanol (5 mL) was added and stirred for 12 hours, and deionized water (1 mL) was added to precipitate a solid powder. After filtration and washing, SAM14 was obtained with a yield of 79%. 1H NMR (400 MHz, DMSO-d 6 )δ7.48(d,J=7.5Hz,4H),7.29-7.23(m,1H),7.08(d,J=7.5Hz,4H),6.88-6.82(m,1H),3.63-3.60(m,2H),2.38(s,6H),2.03-2.00(m,2H).
[0180]
[0181] The present application also provides a method for preparing SAM15, specifically:
[0182] Step 1: Compound 24 (1 mmol), compound 31 (1.1 mmol), tetrakis(triphenylphosphine palladium (0)), potassium carbonate aqueous solution (2 M, 5 mL), and toluene (10 mL) were mixed, and heated at 110 degrees Celsius for 48 hours under nitrogen protection. The product compound 32 was separated by silica gel chromatography column with a yield of 76%. 1 H NMR (400 MHz, DMSO-d 6 )δ8.21(s,2H),8.02(d,J=7.5Hz,2H),7.80-7.72(m,6H),7.55(d,J=7.5Hz,2H),7.49(d,J=7.5Hz,4 H),7.37(d,J=7.5Hz,2H),7.08(d,J=7.5Hz,4H),4.33-4.29(m,2H),2.38(s,6H),1.30-1.26(m,3H).
[0183] Step 2: Compound 32 (1 mmol) was dissolved in tetrahydrofuran (THF, 10 mL), and sodium hydroxide aqueous solution (NaOH aq, 2 M, 10 mL) was added. After heating at 75 °C for 20 h, dilute hydrochloric acid was added to acidify, and the precipitate was filtered and washed to obtain the product SAM15 with a yield of 79%. 1 H NMR (400 MHz, DMSO-d 6 )δ12.71(s,1H),8.21(s,2H),8.02(d,J=7.5Hz,2H),7.85-7.80(m,4H),7.67(d,J=7.5Hz,2H),7.55 (d, J=7.5Hz, 2H), 7.49 (d, J=7.5Hz, 4H), 7.37 (d, J=7.5Hz, 2H), 7.08 (d, J=7.5Hz, 4H), 2.38 (s, 6H).
[0184]
[0185] The present application also provides a method for preparing SAM16, specifically:
[0186] Step 1: Compound 33 (1 mmol), compound 2 (8 mL), 50% potassium hydroxide aqueous solution (KOH (aq), 5 mL), and tetrabutylammonium bromide (TBAB, 5% mmol) were mixed, heated at 70 degrees Celsius for 20 hours under nitrogen protection, and separated by silica gel chromatography column to obtain compound 34 with a yield of about 65%. 1 H NMR (400 MHz, CDCl 3 )δ7.82-7.78(m,4H),7.54-7.51(m,2H),7.36-7.33(m,20H),4.18-4.14(m,2H),3.54-3.50(m,2H),1.83-1.72(m,4H).
[0187] Step 2: Compound 34 (0.8 mmol), triethyl phosphite (P(OEt) 3 , 10 mL) were mixed, heated at 180 degrees Celsius for 12 hours under nitrogen protection, and triethyl phosphite was removed by reduced pressure distillation. The crude product was mixed with tributylsilane bromide (TMSBr, 0.72 mmol) and 1,4-dioxane (5 mL), stirred at room temperature for 20 hours under nitrogen protection, and the solvent was removed. Methanol (5 mL) was added and stirred for 12 hours, and deionized water (1 mL) was added to precipitate solid powder. SAM16 was obtained after filtration and washing, with a yield of about 59%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.82-7.78(m,4H),7.54-7.51(m,2H),7.36-7.33(m,20H),4.18-4.14(m,2H),1.74-1.66(m,4H),1.28-1.24(m,2H).
[0188]
[0189] The present application also provides a method for preparing SAM17, specifically:
[0190] Step 1: Compound 35 (1 mmol), compound 2 (8 mL), 50% potassium hydroxide aqueous solution (KOH (aq), 5 mL), and tetrabutylammonium bromide (TBAB, 5% mmol) were mixed, heated at 70 degrees Celsius for 20 hours under nitrogen protection, and separated by silica gel chromatography column to obtain compound 36 with a yield of about 65%. 1 H NMR (400 MHz, CDCl 3)δ7.82-7.78(m,4H),7.54-7.51(m,2H),4.18-4.14(m,2H),3.54-3.50(m,2H),1.83-1.72(m,4H),0.92(s,6H).
[0191] Step 2: Compound 36 (0.8 mmol), triethyl phosphite (P(OEt) 3 , 10 mL) were mixed, heated at 180 degrees Celsius for 12 hours under nitrogen protection, and triethyl phosphite was removed by reduced pressure distillation. The crude product was mixed with tributylsilyl bromide (TMSBr, 0.72 mmol) and 1,4-dioxane (5 mL), stirred at room temperature for 20 hours under nitrogen protection, and the solvent was removed. Methanol (5 mL) was added and stirred for 12 hours, and deionized water (1 mL) was added to precipitate solid powder. SAM17 was obtained after filtration and washing, with a yield of about 59%. 1 H NMR (400 MHz, DMSO-d 6 )δ7.82-7.78(m,4H),7.54-7.51(m,2H),7.36-7.33(m,20H),4.18-4.14(m,2H),1.74-1.66(m,4H),1.28-1.24(m,2H),0.92(s,6H).
[0192]
[0193] The preparation method of the above-mentioned SAM1 to SAM17 provided in the embodiments of the present application has low cost and high yield.
[0194] The self-assembling material provided in the embodiment of the present application includes a first self-assembling molecular material and a second self-assembling molecular material. The first self-assembling molecular material is the first self-assembling molecular material introduced in the above embodiment, which will not be repeated. The second self-assembling molecular material includes at least one of oxygen atoms and nitrogen atoms containing unbonded lone pairs of electrons; it can be understood that the second self-assembling molecular material can be understood as a self-assembling material commonly used in the prior art. The self-assembling material formed by mixing the first self-assembling molecular material and the second self-assembling molecular material is used to passivate the lead atoms of the perovskite, which can achieve a better passivation effect and is beneficial to improve the photoelectric conversion efficiency and stability of the solar cell 100. The perovskite battery has a larger open circuit voltage, short-circuit current density and fill factor, a higher photoelectric conversion efficiency, and better stability.
[0195] In one embodiment, the second self-assembling molecular material is any one of the following compounds M1 to M4:
[0196]
[0197] In one embodiment, the first self-assembling molecular material accounts for 20%-80% of the self-assembling material. Optionally, in the self-assembling material, the second self-assembling molecular material is the main component, and the first self-assembling molecular material is used as an additive. A small amount of the first self-assembling molecular material is added to the second self-assembling molecular material, which is beneficial to improve the passivation effect and has a higher photoelectric conversion efficiency. Optionally, in the self-assembling material, the first self-assembling molecular material is the main component, and the second self-assembling molecular material is used as an additive. A small amount of the second self-assembling molecular material is added to the first self-assembling molecular material, which is beneficial to improve the passivation effect and has a higher photoelectric conversion efficiency.
[0198] It should be noted that the second self-assembling molecular material in the self-assembling material provided in the embodiment of the present application is an optional material, that is, the self-assembling material provided in the embodiment of the present application may only include the first self-assembling molecular material, and the specific design is based on needs.
[0199] In one embodiment, the hole transport layer includes the self-assembly material provided in the examples of the present application.
[0200] Optionally, the hole transport layer only includes self-assembly materials, and the self-assembly materials form a hole transport layer. As a hole transport material, the self-assembly material can realize hole transport while passivating the interface defects of the light absorption layer, which can reduce the film structure of the solar cell and reduce the thickness, so that the solar cell has a higher photoelectric conversion efficiency and better stability. In a specific implementation, the thickness of the hole transport layer formed by the self-assembly material is 0.1nm-5nm, and it has good self-assembly performance; a molecular size of the self-assembly material is greater than or equal to 0.1nm, and the thickness is less than 0.1nm, and it may not be able to form a continuous film structure; the thickness is greater than 5nm, which affects the self-assembly performance. The thickness of the hole transport layer formed by the self-assembly material is 0.1nm-5nm, the specific surface area is large, the utilization rate of the coordinated atoms is high (that is, each site is used for coordination as much as possible), and it has a good passivation effect and self-assembly performance. Exemplarily, the thickness of the hole transport layer formed by the self-assembled material is 0.1 nm, 0.5 nm, 1 nm, 1.5 nm, 2.0 nm, 2.5 nm, 3.0 nm, 3.5 nm, 4.0 nm, 4.5 nm, 5.0 nm, or a range consisting of any two of the above values, for example, 0.5 nm-4 nm, 1.0 nm-5 nm, etc.
[0201] Optionally, the hole transport layer includes a self-assembled material and a metal oxide, and the self-assembled material is attached to the surface of the metal oxide. Among them, the metal oxide includes but is not limited to at least one of nickel oxide, molybdenum oxide, and tungsten oxide. In other words, the hole transport layer includes a mixed material of the self-assembled material and the metal oxide. The self-assembled material can passivate the surface of the metal oxide while passivating the interface defects of the light absorption layer, so that the solar cell has a larger open circuit voltage, short circuit current density and fill factor, which is beneficial to improve the photoelectric conversion efficiency and stability of the solar cell.
[0202] Optionally, the hole transport layer includes a self-assembled material layer and a metal oxide layer which are stacked, and the self-assembled material layer is arranged on one side of the metal oxide layer close to the light absorption layer 13. The self-assembled material layer includes a self-assembled material. The metal oxide layer includes a metal oxide. While the self-assembled material passivates the interface defects of the light absorption layer, it can also passivate the surface of the metal oxide, which is beneficial to improve the photoelectric conversion efficiency and stability of the solar cell. In a specific implementation, the thickness of the metal oxide layer is 10nm-100nm, which can achieve a good hole transport effect. In a specific implementation, the metal oxide includes but is not limited to at least one of nickel oxide, molybdenum oxide, and tungsten oxide. In a specific implementation, the thickness of the self-assembled material layer is 0.1nm-5nm, the specific surface area is large, the utilization rate of the coordinated atoms is high, and it has a good passivation effect and self-assembly performance. Exemplarily, the thickness of the self-assembled material layer is 0.1 nm, 0.5 nm, 1 nm, 1.5 nm, 2.0 nm, 2.5 nm, 3.0 nm, 3.5 nm, 4.0 nm, 4.5 nm, 5.0 nm, or a range consisting of any two of the above values, for example, 0.5 nm-4 nm, 1.0 nm-5 nm, etc.
[0203] In one embodiment, the material of the passivation layer includes the self-assembled material provided in the embodiment of the present application. The self-assembled material can be used as an independent passivation layer to passivate the low-coordinated lead vacancies in the light absorbing layer, reduce the defects on the interface of the light absorbing layer, and make the solar cell have higher photoelectric conversion efficiency and better stability. It should be noted that the material of the hole transport layer at this time can include the self-assembled material, or it can be a material in the prior art.
[0204] Optionally, the thickness of the passivation layer formed by the self-assembly material provided in the embodiment of the present application is 0.1nm-5nm, with a large specific surface area, a high utilization rate of coordinated atoms, and good passivation effect and self-assembly performance. Exemplarily, the thickness of the passivation layer formed by the self-assembly material is 0.1nm, 0.5nm, 1nm, 1.5nm, 2.0nm, 2.5nm, 3.0nm, 3.5nm, 4.0nm, 4.5nm, 5.0nm, or a range consisting of any two of the above values, for example, 0.5nm-4nm, 1.0nm-5nm, etc.
[0205] It should be noted that the hole transport layer includes a self-assembly material, or the passivation layer disposed between the hole transport layer and the light absorption layer 13 includes a self-assembly material, so that the solar cell includes a self-assembly material.
[0206] When the hole transport layer of the solar cell 100 includes the above-mentioned self-assembly material (at this time, the hole transport layer only includes the self-assembly material, or the hole transport layer includes a metal oxide and a self-assembly material attached to the surface of the metal oxide, or the hole transport layer includes a metal oxide layer and a self-assembly material layer stacked), the self-assembly material can be directly dissolved in an organic solvent and covered on the surface of the first electrode 11 or the metal oxide by spin coating, spraying, scraping, slit coating or roll-to-roll printing, or the first electrode 11 or the metal oxide surface is immersed in a self-assembly material solution, and the solute molecules in the self-assembly material solution self-assemble on the surface of the first electrode 11 or the metal oxide to form a monomolecular film. The solvent for dissolving the self-assembly material can be at least one of methanol, isopropanol, ethanol, and chlorobenzene, with a concentration of 0.1 mg / mL-10 mg / mL. After the self-assembly material is prepared on the surface of the first electrode 11 or the metal oxide, the solvent can be removed by annealing or vacuum.
[0207] When the self-assembly material described above is used as a hole transport layer (ie, the hole transport layer only includes the self-assembly material), the preparation method of the solar cell 100 is:
[0208] Step 1: Etch and clean the transparent electrode substrate, dry it for later use, and form the first electrode 11.
[0209] Step 2: Cover the self-assembled material on a clean transparent electrode substrate, remove the solvent by annealing or vacuum, obtain a self-assembled monolayer, and form a hole transport layer (i.e., the first transport layer 12). Optionally, the self-assembled material includes a first self-assembled molecular material. Optionally, the self-assembled material includes a first self-assembled molecular material and a second self-assembled molecular material.
[0210] Step 3: Prepare a perovskite light absorbing layer on the self-assembled monolayer for later use to form a light absorbing layer 13 .
[0211] Step 4: a blocking layer 16 and an electron transport layer (ie, the second transport layer 14 ) are sequentially prepared on the perovskite light absorbing layer for later use.
[0212] Step 5: Prepare an electrode layer on the electron transport layer to form a second electrode 15, and perform an edge cleaning test.
[0213] When the self-assembled material is attached to the metal oxide and serves as a hole transport layer (ie, the hole transport layer includes the metal oxide and the self-assembled material attached to the surface of the metal oxide), the preparation method of the solar cell 100 is:
[0214] Step 1: Etch and clean the transparent electrode substrate, dry it for later use, and form the first electrode 11.
[0215] Step 2: Covering a clean transparent electrode substrate with a metal oxide to obtain a metal oxide film; optionally, the metal oxide is NiO x .
[0216] Step 3: Cover the above self-assembled material on NiO x On the substrate, the solvent is removed by annealing or vacuum to obtain a self-assembled monolayer to form a hole transport layer (i.e., the first transport layer 12). Optionally, the self-assembled material includes a first self-assembled molecular material. Optionally, the self-assembled material includes a first self-assembled molecular material and a second self-assembled molecular material.
[0217] Step 4: Prepare a perovskite light absorbing layer on the self-assembled monolayer for later use to form a light absorbing layer 13 .
[0218] Step 5: A blocking layer 16 and an electron transport layer (ie, the second transport layer 14 ) are sequentially prepared on the perovskite light absorbing layer for later use.
[0219] Step 6: Prepare an electrode layer on the electron transport layer to form a second electrode 15, and perform an edge cleaning test.
[0220] The embodiment of the present application also provides an electrical device, which is a common device including the solar cell of the present application, such as the communication field, transportation field, industrial and agricultural field, lighting field, etc. The electrical device may include, for example, satellites, communication equipment, traffic lights, lighthouses, wireless telephone booths, monitoring equipment in the drilling field, power supply systems, camping lights, electric vehicles, electronic equipment chargers, etc.
[0221] The beneficial effects of the present application are further illustrated below in conjunction with embodiments.
[0222] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0223] Embodiment 1:
[0224] (1) FTO conductive glass cleaning
[0225] Take 20 pieces of FTO conductive glass with a size of 2.0×2.0cm, remove 0.35cm of FTO at both ends by laser etching, and expose the glass substrate. Ultrasonic clean the etched FTO conductive glass several times with water, acetone, and isopropanol in turn. Blow dry the solvent of the FTO conductive glass under a nitrogen gun and put it into a UV ozone machine for further cleaning.
[0226] (2) Preparation of hole transport layer
[0227] A methanol solution of nano nickel oxide (10 mg / mL) was spin-coated on the surface of FTO conductive glass at 2000 rpm, and the solvent was removed by vacuum or annealing to form a nickel oxide film. The self-assembly material SAM1 was dissolved in methanol to obtain a self-assembly material solution. The self-assembly material was spin-coated on the surface of the nickel oxide film at 3000 rpm, and a self-assembly material layer was obtained by vacuum or annealing.
[0228] (3) Preparation of perovskite layer
[0229] Lead iodide (726 mg), iodoformamide (240 mg), cesium iodide (19 mg), and lead bromide (11 mg) were weighed and dissolved in 1 mL of a mixed solution of DMF and DMSO (4:1), stirred for 3 h, filtered with a 0.22 μm organic filter membrane to obtain a perovskite precursor solution, and the perovskite precursor solution was spin-coated on the obtained self-assembled material layer at 3000 rpm / s, annealed at 100°C for 30 min, and cooled to room temperature, wherein the active material of the perovskite absorption layer is the CsFA system.
[0230] (4) Preparation of PC 61 BM electron transport layer, barrier layer 16 and Cu electrode
[0231] The electron transport layer PC was spin-coated on the perovskite layer at 1500 rpm / s 61BM (20 mg / mL chlorobenzene solution), annealed at 100°C for 10 min, and then spin-coated with a barrier layer 16 (BCP saturated isopropanol solution) at 5000 rpm / s. The obtained wafer is placed in an evaporator to evaporate the metal electrode Cu.
[0232] The preparation process of Comparative Examples 1 to 2 and Examples 2 to 17 is similar to that of Example 1, except that the self-assembly materials are different, as shown in Table 1. The preparation process of Example 18 is similar to that of Example 1, except that during the preparation of the hole transport layer, no nickel oxide film is formed, and the self-assembly material is directly spread on the FTO surface. The preparation process of Example 19 is similar to that of Example 1, except that the self-assembly material in Example 19 is a mixture of SAM1 and M1 (mass ratio 1:1), which are dissolved in methanol together.
[0233] The relevant parameter testing process of the embodiments and comparative examples of the present application is as follows:
[0234] (1) IV measurement method:
[0235] The solar simulator of Guangyan was used, and the national standard IEC61215 was used for testing. The light intensity was calibrated with a crystalline silicon solar cell to reach a solar intensity, AM 1.5. The sample cell was connected to a digital source meter, and its photoelectric conversion efficiency was measured under illumination. Among them, the optimal photoelectric conversion efficiency refers to the photoelectric conversion efficiency achieved after the solar cell is prepared and aged. AM1.5 is the solar spectrum obtained per unit area in the direction of solar incidence when the actual distance of sunlight passing through the atmosphere is 1.5 times the vertical thickness of the atmosphere.
[0236] Hole transport layer Optimum photoelectric conversion efficiency / % Photovoltaic conversion efficiency on the 30th day / % Example 1 SAM1+Nickel Oxide 25.22 24.28 Example 2 SAM2+ Nickel Oxide 24.81 24.15 Example 3 SAM3+Nickel Oxide 24.79 24.00 Example 4 SAM4+Nickel Oxide 24.93 24.03 Example 5 SAM5+Nickel Oxide 24.75 24.04 Example 6 SAM6+Nickel Oxide 24.88 23.88 Example 7 SAM7+Nickel Oxide 24.61 23.89 Example 8 SAM8+Nickel Oxide 25.19 24.16 Example 9 SAM9+Nickel Oxide 24.91 24.01 Example 10 SAM10+Nickel Oxide 25.06 24.21 Embodiment 11 SAM11+nickel oxide 24.80 24.09 Example 12 SAM12+Nickel Oxide 25.00 24.16 Embodiment 13 SAM13+Nickel Oxide 24.86 24.19 Embodiment 14 SAM14+Nickel Oxide 24.79 23.66 Embodiment 15 SAM15+Nickel Oxide 24.87 24.14 Example 16 SAM16+nickel oxide 24.61 23.99 Embodiment 17 SAM17+Nickel Oxide 24.79 23.86 Embodiment 18 SAM1 24.79 24.13 Embodiment 19 SAM1+M1+nickel oxide 25.02 24.09 Comparative Example 1 Nickel Oxide 19.05 16.68 Comparative Example 2 M1 23.13 22.05
[0237] As can be seen from Table 1, the photoelectric conversion efficiency and stability of the solar cell are significantly improved by using the self-assembly material provided in the embodiment of the present application, compared with Comparative Example 1 (no self-assembly material is used) and Comparative Example 2 (using the self-assembly material in the prior art).
[0238] The above description is only an implementation method of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A self-assembling material, characterized in that: It includes a first self-assembling molecular material, wherein the structural formula of the first self-assembling molecular material is Wherein, Ar represents an aromatic group, Ar includes at least one coordinating atom, the coordinating atom includes an unbonded lone pair of electrons, and the coordinating atom includes one or more of a phosphorus atom, an arsenic atom, a sulfur atom, and a selenium atom; L includes one or more of a carbon-containing group, a nitrogen-containing group, an oxygen-containing group, a silicon-containing group, a phosphorus-containing group, and a sulfur-containing group, and the value of n is 0-10; A includes a hydrophilic group.
2. The self-assembly material according to claim 1, characterized in that Ar includes two or more of the above-mentioned coordinating atoms.
3. The self-assembly material according to claim 1 or 2, characterized in that: The Ar is any one of the following Ar1 to Ar12: wherein X1 to X5 are selected from any one of -CR"2-, -NR"-, -O-, -SiR"2-, -PR"-, -S-, -As-, -Se-, -C(=O)-, -C(=S)-, -C(=NR")-, -C(=CR"2)-, and m is 1-3; R1 to R 143 and R" are independently selected from any one of hydrogen, halogen, -OR', -OCOR', -NHCOR', -NR'2, R', halogen-substituted R', -SR', -PR'2, -AsR'2, -Se-; R' is any one of a substituted or unsubstituted phenyl group, a thienyl group, and a C1-C5 alkyl group.
4. The self-assembly material according to claim 3, characterized in that: When Ar is Ar1, at least one of R1 to R8 is selected from -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar2, R9 to R 18 At least one of them is selected from -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar3, R 19 To R 30 At least one of them is selected from -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar4, R 31 To R 44 At least one of them is selected from -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar5, R 45 To R 60 At least one of them is selected from -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar6, R 61 To R 78 At least one of them is selected from -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar10, and X1 does not contain a group of phosphorus, sulfur, arsenic, or selenium, R 127 To R 134 At least one of them is selected from -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar11, and X2 to X3 do not contain phosphorus, sulfur, arsenic, or selenium, R 135 To R 138 At least one of them is selected from -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar12, and X4 to X5 do not contain groups of phosphorus, sulfur, arsenic, or selenium, R 139 To R 143 At least one of them is selected from -PR'2, -SR', -AsR'2, and -Se-.
5. The self-assembly material according to claim 3 or 4, characterized in that: When Ar is Ar1, at least two of R1 to R8 are selected from -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar2, R9 to R 18 At least two of them are selected from one of -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar3, R 19 To R 30 At least two of them are selected from one of -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar4, R 31 To R 44 At least two of them are selected from one of -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar5, R 45 To R 60 At least two of them are selected from one of -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar6, R 61 To R 78 At least two of them are selected from one of -PR'2, -SR', -AsR'2, -Se-; and / or, When Ar is Ar7, R 79 To R 92 At least one of -PR'2, -SR', -AsR'2, -Se- is selected from one of them; and / or, When Ar is Ar8, R 93 To R 108 At least one of -PR'2, -SR', -AsR'2, -Se- is selected from one of them; and / or, When Ar is Ar9, R 109 To R 126 At least one of -PR'2, -SR', -AsR'2, -Se- is selected from one of them; and / or, When Ar is Ar10 and X1 does not contain phosphorus, sulfur, arsenic, or selenium, R 127 To R 134 At least two of them are selected from -PR'2, -SR', -AsR'2, -Se-; or when Ar is Ar10 and X1 contains one of phosphorus, sulfur, arsenic, and selenium groups, R 127 To R 134 At least one of -PR'2, -SR', -AsR'2, -Se- is selected from one of them; and / or, When Ar is Ar11 and X2 to X3 do not contain phosphorus, sulfur, arsenic, or selenium, R 135 To R 138 At least two of them are selected from -PR'2, -SR', -AsR'2, -Se-; or when Ar is Ar11 and X2 to X3 contain one of phosphorus, sulfur, arsenic, and selenium groups, R 135 To R 138 At least one of -PR'2, -SR', -AsR'2, -Se- is selected from one of them; and / or, When Ar is Ar12 and X4 to X5 do not contain phosphorus, sulfur, arsenic, or selenium, R 139 To R 143 At least two of them are selected from -PR'2, -SR', -AsR'2, -Se-; or when Ar is Ar12 and X4 to X5 contain one of phosphorus, sulfur, arsenic, and selenium groups, R 139 To R 143 At least one of them is selected from -PR'2, -SR', -AsR'2, and -Se-.
6. The self-assembly material according to any one of claims 1 to 5, characterized in that: The hydrophilic group includes one or more oxoacid groups.
7. The self-assembly material according to claim 6, characterized in that: The oxygen acid group includes any one of -COOH, a salt corresponding to -COOH, -PO(OH)2, a salt corresponding to -PO(OH)2, -PHO(OH), a salt corresponding to -PHO(OH), -SO2(OH), a salt corresponding to -SO2(OH), and -B(OH)2, a salt corresponding to -B(OH)2.
8. The self-assembly material according to any one of claims 1 to 7, characterized in that: L is -CR"2-, -NR"-, -O-, -SiR"2-, -PR"-, -S-, -C(=O)-, -C(=S)-, -C(=NR")-, -C(=CR"2)-, and at least one of the following L1 to L8; Among them, Z1 to Z 40 Each independently selected from =CR”-, =N-; X6 to X 11 Any one selected from -CR"2-, -NR"-, -O-, -SiR"2-, -PR"-, -S-, -As-, -Se-, -C(=O)-, -C(=S)-, -C(=NR")-, -C(=CR"2)-; R" is selected from any one of hydrogen, halogen, -OR', -OCOR', -NHCOR', -NR'2, R', halogen-substituted R', -SR', -PR'2, -AsR'2, -Se-; R' is any one of a substituted or unsubstituted phenyl group, a thienyl group, and a C1-C5 alkyl group.
9. The self-assembly material according to claim 1, characterized in that: The first self-assembling molecular material is selected from any one of SAM1 to SAM17:
10. The self-assembly material according to any one of claims 1 to 9, characterized in that: The invention also includes a second self-assembling molecular material, wherein the second self-assembling molecular material includes at least one of oxygen atoms and nitrogen atoms containing unbonded lone pairs of electrons.
11. The self-assembly material according to any one of claims 10, characterized in that: The second self-assembling molecular material is selected from any one of the following compounds M1 to M4:
12. A solar cell, characterized in that: The self-assembly material comprises the self-assembly material according to any one of claims 1 to 11.
13. The solar cell according to claim 12, characterized in that: It comprises a light absorbing layer and a passivation layer located on one side of the light absorbing layer, wherein the passivation layer comprises the self-assembly material.
14. The solar cell according to claim 12, characterized in that: It comprises a light absorbing layer and a hole transport layer located on one side of the light absorbing layer, wherein the hole transport layer comprises the self-assembly material.
15. The solar cell according to claim 14, characterized in that: The hole transport layer further comprises a metal oxide; Optionally, the self-assembled material is attached to the surface of the metal oxide.
16. The solar cell according to claim 14, characterized in that: The hole transport layer comprises a self-assembly material layer and a metal oxide layer which are stacked, wherein the self-assembly material layer comprises the self-assembly material, and the metal oxide layer comprises a metal oxide.
17. The solar cell according to claim 16, characterized in that: The thickness of the self-assembly material layer is 0.1nm-5nm.
18. The solar cell according to claim 16, characterized in that: The metal oxide includes at least one of nickel oxide, molybdenum oxide and tungsten oxide; and / or the thickness of the metal oxide layer is 10-100 nm.
19. The solar cell according to claim 12, characterized in that: The light absorbing layer includes a perovskite material, wherein the chemical formula of the perovskite material is ABX3 or A2CDX6, wherein A is at least one of MA, FA, and Cs, B is at least one of Pb and Sn, C is Ag+, and D is Bi 3+ , Sb 3+ 、In 3+ At least one of, X is at least one of Br and I.
20. The solar cell according to claim 19, characterized in that The band gap of the light absorbing layer is 1.20 eV-2.30 eV; and / or the thickness of the light absorbing layer is 200 nm-1000 nm.
21. The solar cell according to claim 19, characterized in that It also includes an electron transport layer, a blocking layer, and a second electrode disposed on one side of the light absorbing layer, and a first electrode disposed on the other side of the light absorbing layer, wherein the blocking layer is located between the electron transport layer and the second electrode; Optionally, the electron transport layer comprises [6,6]-phenyl-C 61 -Butyric acid methyl ester, [6,6]-phenyl-C 71 - at least one of methyl butyrate, fullerene C60, fullerene C70, tin dioxide, zinc oxide, perylene imide materials, and naphthylimide materials, and / or the thickness of the electron transport layer is 5nm-100nm; Optionally, the barrier layer includes 2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline, SnO2, ZnO, CeO x At least one of the following, and / or the thickness of the barrier layer is 0.5nm-20nm; Optionally, the second electrode comprises at least one of Ag, Cu, C, Au, Al, ITO, AZO, BZO, and IZO, and / or the thickness of the second electrode is 10 nm-1000 nm; Optionally, the first electrode includes at least one of FTO, ITO, AZO, BZO, and IZO, and / or the thickness of the first electrode is 10 nm-1000 nm.
22. An electrical equipment, characterized in that: A solar cell comprising the solar cell according to any one of claims 12 to 21.
Citation Information
Cited By
Perovskite photovoltaic device based on self-assembled monomolecular layer and preparation method thereof
CN119698162A
Self-assembled single-layer perovskite solar cell and preparation method thereof
CN120456722A
Flexible electroluminescent wire and hole injection material
CN120813186A
Flexible electroluminescent line and hole injection material
CN120813186B
Perovskite photovoltaic device and preparation method thereof
CN121001548A